Rogowsky coil applications for power measurement under non-sinusoidal field conditions - Diahovchenko, Illia; Mykhailyshyn, Roman; Danylchenko, Dmytro; Shevchenko, Serhii (Lietuvos mokslų akademija, Lithuania, 2019)
Electric energy measurement errors depend on the design and algorithms used in electricity meters, as well as on the auxiliary and embedded sensors’ accuracy and bandwidth (or more precisely, maximum measurable frequency). Poor power quality may affect the electric energy meters accuracy, which will lead to the improper power accounting. In this article the applications of the Rogowsky coil sensors for electric energy measurement are studied. The advantages and the challenges of this sensor type implementation are discussed, and the operation scheme of the power meter for the separate measurement of the fundamental harmonic’s electric energy and the higher harmonics electric energy is proposed. The possibility of implementation of responsibility determining methods for power quality distortion is highlighted.
Keywords: Rogowsky coil; power measurement; higher harmonics; power quality; current transducer; power quality distortion